(untitled) (Ustozlar uchun, 2026)
This paper explores the geographical features, economic development, and social structure of Australia. Australia is one of the most developed countries in the world, known for its strong economy, high standard of living, and unique natural environment. The study is based on secondary sources and provides an overview of key factors that contribute to the country’s development. The findings show that mining, agriculture, education, and tourism play an important role in Australia’s economy, while urbanization and immigration shape its social structure. Despite some environmental and urban challenges, Australia remains one of the most livable countries globally.